GETTING INEBRIATED IN THE TAVERN: REMINISCENCES OF POE IN ÁLVARES DE AZEVEDO - Silva, Lucélia Magda Oliveira da; Sales Araújo, Naiara (REVISTA DE LETRAS - JUÇARA, 2019)
Romanticism, initiated in eighteenth-century Europe, had, among other characteristics, the overestimation of emotions and the elaboration of a social critique based on pre-defined customs and values. In America, Romanticism established itself, primarily, in the United States, where Edgar Allan Poe was one of its main figures, whose pessimist and macabre works were translated by Baudelaire; and, afterwards, in Brazil, the need to build a literature that had its own nationality, even if still under the influence of the French molds. Therefore, the translations of Poe’s tales made by Baudelaire came to Brazil and served as inspiration for many established authors. By observing concomitant aspects in the prose of both Poe and Álvares de Azevedo, whose work Noite na Taverna (1997) is regarded as one of the first pieces of fantastic literature in Brazil, our article aims to verify the possible influence of the American author on the work of Azevedo, using the studies held by Alfredo Bosi, Antônio Candido, Todorov and Roas, as well as consolidated literary reviews on Edgar A. Poe. Keywords: Edgar Allan Poe. Álvares de Azevedo. Romanticism. Noite na Taverna.